PUTUSAN BEBAS DALAM PERKARA TINDAK PIDANA KORUPSI TIDAK MENGHAPUSKAN HAK UNTUK MENUNTUT KERUGIAN TERHADAP KEUANGAN NEGARA - AMIRUDIN, SH. A.2021131029, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2016)
ABSTRACTCorruption that occurred during this time in addition to financial harm and thecountry's economy also inhibits the growth and sustainability of nationaldevelopment, may hinder the stability and national security, corruption is a complexcrime and social implications to others because it concerns the rights of others toobtain the same prosperity. Even corruption can be termed as a social sin which asin or a crime committed and the impact for many people, the value of sinfulness fargreater than the sin of personal nature. One element in corruption in Article 2paragraph (1) and Article 3 of Law No. 31 of 1999. On Combating Corruption is thefinancial loss the country / economy of the country is done unlawfully. tate loss canoccur because of a violation of law or negligence of state officials or public servantsinstead of treasurer in the framework of the implementation of the administrativeauthority or by the treasurer in the framework of the implementation of the treasuryauthority. Completion of state losses needs to be done to restore the country's wealthis lost or reduced, and increase discipline and responsibility of civil servants / officialsof the state in general, and financial managers in particular.Against the acquittal orescape from any such lawsuits based on the provisions of Article 32 paragraph (2) ofLaw No. 31 of 1999. as amended by Act No. 20 of 2001 on Corruption Eradicationsaid: